From Asian Maritime Cultural Routes to Peace: The View of Zheng He Cultural Route Heritage - Li Pei Feng (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2026)
Asian maritime networks linking East Asia to the Indian Ocean fostered centuries of commercial exchange, religious circulation, and cultural transmission. Archaeological remains, documentary traditions, ritual practices, and shared artistic forms demonstrate the vitality of these routes as dynamic cultural systems rather than mere trading corridors. Melaka and Semarang, cities long associated with Zheng He’s voyages, provide compelling examples of how maritime heritage persists through both material traces and living traditions. Viewed through the framework of cultural route world heritage, these networks contributed significantly to processes of Islamization, inter-civilizational dialogue, and regional integration. Their historical patterns offer contemporary pathways for peacebuilding, cooperation, and heritage-based community development.